2016
DOI: 10.1080/1828051x.2016.1241133
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofTrichodermafermented wheat bran on growth performance, intestinal morphology and histological findings in broiler chickens

Abstract: This experiment investigated the effects of wheat bran fermented with Trichoderma pseudokoningii (FWB) on growth performance, intestinal morphology and the incidence of non-specific pathological lesions in broilers. In vitro experimental results showed that cellulase and xylananse activity of fermented wheat bran reached its peak at day 4 and solid-state fermentation (SSF) enhanced the reducing sugar content. In addition, the possibility of Trichoderma adhering to the broiler's crop epitheliums was also discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 30 publications
8
39
0
Order By: Relevance
“…Similar positive effect on growth parameters of broilers was recorded in the study performed by Chu et al (2017) after feeding with fermented wheat bran. The wheat brans were fermented by Trichoderma pseudokoningii.…”
Section: Resultssupporting
confidence: 69%
“…Similar positive effect on growth parameters of broilers was recorded in the study performed by Chu et al (2017) after feeding with fermented wheat bran. The wheat brans were fermented by Trichoderma pseudokoningii.…”
Section: Resultssupporting
confidence: 69%
“…These results were in accordance with Yi et al (2016) who revealed that, the number of coliform bacteria was decreased in the ilea and caeca of ASSESSMENT OF THE PERFORMANCE OF CHICKS FED WITH WHEAT BRAN broilers supplemented with 10% fermented wheat bran (FWB) with Trichoderma pseudokonngii compared to the control group. Lactobacilli count at the 35 th day of age was significantly increased to 8.71 log CFU/g cecum content in birds fed with wheat bran solid fermented by Trichoderma longibrachiatum (SF1), compared to diet with no wheat bran (control 1) and diet with 10% unfermented WB (control 2) which recorded 8.17 and 8.43 log CFU/g cecum content respectively, ( Table 9).…”
Section: Resultssupporting
confidence: 80%
“…Accordingly, production efficiency factor was highly increased by fermentation of wheat bran and using fermented substrate in broiler feed resulted 196 production efficiency factor compared to 106.5 in control 1 and 161.6 in control 2 as presented in Table 8. Yi et al (2016) suggested that replacing 10% of a basal diet with fermented wheat bran (FWB) by Trichoderma pseudokoningii could not only improve growth performance and nutrient contents but also had economical benefits. This was in agreement with the present study which showed high economical efficiency and production efficiency factor of fermented wheat bran compared to control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations